2019
DOI: 10.1177/0844562119851332
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Patients’ Experiences of Pain Management in the Emergency Department

Abstract: Background Despite management of acute pain, concerns regarding pain are still prevalent in the emergency department (ED). Purpose This study aimed to explore the factors influencing patients’ pain management in a Jordanian ED. Method Fifteen semistructured interviews (N = 15) with purposively selected patients in the ED. Results The thematic analysis uncovered two related themes. The first theme described the stage of “being on ED bed” which encapsulates two subthemes: “bad pain means, bad diagnosis” and “smi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Yet, there was also some evidence of discussion, suggesting patient involvement and partnership in their ED care. Patient experiences were optimised when care providers delivered the right amount of information in an understandable way, [35-37, 47, 50-55, 57, 58, 60-62, 65, 67, 69, 70, 75-78] when they communicated with empathy and compassion, [47,49,56,68,69,79] when patients were informed about care processes and treatment options, [46,49,52,56,62,65,68,69,72,80] updated throughout their ED journey, [39,66,69] were able to discuss matters that were important to them, [35-37, 47, 52, 54, 67, 68] and were encouraged to talk and ask questions. [50,65,69] Generally, patients who felt informed by their care providers, reported better experiences characterised by feeling reassured, safe and confident.…”
Section: Communicating With Patients To Keep Them Informedmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, there was also some evidence of discussion, suggesting patient involvement and partnership in their ED care. Patient experiences were optimised when care providers delivered the right amount of information in an understandable way, [35-37, 47, 50-55, 57, 58, 60-62, 65, 67, 69, 70, 75-78] when they communicated with empathy and compassion, [47,49,56,68,69,79] when patients were informed about care processes and treatment options, [46,49,52,56,62,65,68,69,72,80] updated throughout their ED journey, [39,66,69] were able to discuss matters that were important to them, [35-37, 47, 52, 54, 67, 68] and were encouraged to talk and ask questions. [50,65,69] Generally, patients who felt informed by their care providers, reported better experiences characterised by feeling reassured, safe and confident.…”
Section: Communicating With Patients To Keep Them Informedmentioning
confidence: 99%
“…Patients valued emotional aspects of care as it made them feel important and understood by their care providers,[40,48,49,65,81] such as when empathy and genuine concern was demonstrated. [38-40, 43, 45, 47, 49, 56, 60, 65, 81, 82, 86] This occurred when care providers used reassuring words, touch and body language,[40,41,47,49,68,79] when they informed patients' family or friends that they were in the ED,[48,49,61,68,75,82] and by ensuring patients did not feel lonely [37,40,48,49,64,68,[80][81][82]. Receiving an inadequate level of emotional support[40, 43,44,49,65,72,73] or follow-up responsibility for and control of patients' care,[39,41,49,61,88] were efficient and responsive,[37,40,41,45,48,49,56,66,…”
mentioning
confidence: 99%
“…The evidence from the literature confirmed that the trusting relationship was essential for pain management, highlighted as a crucial component in the model for PCPM. This relationship was described as based on mutual understanding within the care team, that is providers, patient and relatives, regarding the cause, experience and management of pain (Aziato & Adejumo, 2015;Brown & McCormack, 2006;Dihle et al, 2006;Idvall et al, 2008;Lauzon Clabo, 2008;Rejeh et al, 2008;Shoqirat, 2014Shoqirat, , 2015Shoqirat et al, 2019Shoqirat et al, , 2020Smith et al, 2006). This was achieved when the nurses truly listened to the patient and trusted the experience (Dihle et al, 2006;Idvall et al, 2008;Rejeh et al, 2008;Shoqirat, 2014).…”
Section: Establish and Maintain A Trusting Relationship Including The...mentioning
confidence: 99%
“…'I was in pain, but her (the nurse) assuring body language made me feel less stressed' (Shoqirat et al, 2020). This was also underlined by a nurse in a study from Iran: 'I try to have a good relationship with them (patient) about pain and suffer, listen to them carefully, and do TA B L E 1 Example from the coding scheme for the individual studies included in the systematic review.…”
Section: Establish and Maintain A Trusting Relationship Including The...mentioning
confidence: 99%
“…Some studies reveal that satisfaction with postoperative pain treatment is less associated with patients’ actual pain experience, but rather with appropriateness of care and involvement in pain management [ 6 ]. The review of abroad literatures reported that conflicting arguments regarding patient satisfaction with pain management in contradict ways [ [7] , [8] , [9] ]. In spite of such studies, there is still limited clinical information available on the association of patient characteristics, patient perception of pain experience, and patient satisfaction with postoperative pain management [ 10 ].…”
Section: Introductionmentioning
confidence: 99%